Therapeutic potential of physical activity in "blue zones" (Blue Space) as a method for correcting depressive ruminations and associated depressive symptoms - A Literature-Based Review - Ivanchuk, Sofiia; Savchak, Tetiana; Kaminskaya, Anhelina; Kurek, Aleksandra; Feretycki, Hubert; Głowacka, Aleksandra; Górecki, Patryk; Kozicki, Maciej; Domińczak, Dominika; Abdulla, Shafea; et al. (Quality in Sport, 2026)
Purpose of research: This literature-based review synthesized current evidence regarding the therapeutic potential of physical activity performed in "blue spaces" (aquatic environments) as a method for correcting depressive ruminations. The study evaluated how the synergy between physical exertion and the unique restorative properties of water impacts mental health, focusing on neurological mechanisms and successful psychological aging in "Blue Zones"Research materials and methods: A structured literature search was conducted in major scientific databases, including PubMed, Scopus, and Google Scholar, for English full-text articles available through 2025. The review utilized the PICOS framework to select high-quality evidence, including Meta-Analyses, Systematic Reviews, and Randomized Controlled Trials examining aquatic interventions in both clinical and healthy populations.Basic results: Engagement in blue spaces leads to a measurable decrease in neural activity within the subgenual prefrontal cortex (sgPFC), the brain region responsible for maladaptive rumination. Aquatic exercise demonstrates superior antidepressant effects compared to land-based activities, with standardized mean differences (SMD) reaching -0.92, particularly for water aerobics. These benefits are supported by the stabilization of the HPA axis, increased BDNF expression, and the "soft fascination" of water, which allows the brain’s executive functions to recover. In "Blue Zones," natural movement near water and strong social ties act as a potent buffer against late-life depression.Conclusions: "Blue Care" is an evidence-based, non-pharmacological intervention that effectively interrupts ruminative thought cycles and improves psychological resilience across the lifespan. Integrating "Blue Prescriptions" into standard psychiatric care and urban planning provides a cost-effective strategy to mitigate mental health disparities and support global well-being